2012
DOI: 10.3109/08039488.2012.748825
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences and willingness-to-pay for ADHD treatment with stimulants using discrete choice experiment (DCE) in Sweden, Denmark and Norway

Abstract: The gap between the monetary valuation of existing products and an optimally valued product suggest that there is room for improvements in the clinical management of ADHD. The results suggest that DCE is a method that can be used to value not only hypothetical scenarios but also can be used to value and distinguish between real-life scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 12 publications
0
40
0
Order By: Relevance
“…However, medication choice varies across patients and is often highly individualized. Medication attributes reported to contribute to the attractiveness of specific pharmacotherapies in adults with ADHD include the ability of the medication to improve function during the work day and into the late afternoon and evening, and a reduced number of doses that need to be taken during the day [11]. In addition, as is the case with other chronic disorders [12], medication adherence among adults with ADHD is negatively influenced by multiple factors that include forgetting to take medication (in part due to the executive function deficits that may be associated with ADHD [13]), the complexity of the treatment regimen (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, medication choice varies across patients and is often highly individualized. Medication attributes reported to contribute to the attractiveness of specific pharmacotherapies in adults with ADHD include the ability of the medication to improve function during the work day and into the late afternoon and evening, and a reduced number of doses that need to be taken during the day [11]. In addition, as is the case with other chronic disorders [12], medication adherence among adults with ADHD is negatively influenced by multiple factors that include forgetting to take medication (in part due to the executive function deficits that may be associated with ADHD [13]), the complexity of the treatment regimen (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The data also demonstrate that parents would prefer a treatment with equal efficacy but no associated risk of abuse or side effects. Previous studies have reported similar findings, whereby efficacy was regarded as the most important attribute; however, side effects and dosing were also identified as key aspects of treatment [13, 14]. ‘Potential of treatment abuse’ was considered an important attribute by parents of adolescents.…”
Section: Discussionmentioning
confidence: 77%
“…Parents preferred an oral, once-a-day therapy (compared with three times daily administration or a transdermal patch), rapid onset of action, and longer duration of ADHD symptom control. Glenngard et al [13] employed DCE to assess the preferences and willingness to pay of 285 patients with ADHD (or the parents of children and adolescents) for different treatment attributes, including symptom control, side effects, dosing and cost. All attributes were significant predictors of choice ( p  < 0.01), with symptom control and side effects considered the most important treatment attributes.…”
Section: Introductionmentioning
confidence: 99%
“…However, parents and caregivers value a broad-based approach to ADHD care management [12, 22, 2427], which often involves school accommodations, parent training, and a pediatric or child psychiatry specialty provider. However, far less is known about preferences for these attributes.…”
Section: Introductionmentioning
confidence: 99%